2020
DOI: 10.1080/21505594.2020.1806675
|View full text |Cite
|
Sign up to set email alerts
|

A DUF4148 family protein produced inside RAW264.7 cells is a critical Burkholderia pseudomallei virulence factor

Abstract: Burkholderia pseudomallei: is the etiological agent of the disease melioidosis and is a Tier 1 select agent. It survives and replicates inside phagocytic cells by escaping from the endocytic vacuole, replicating in the cytosol, spreading to other cells via actin polymerization and promoting the fusion of infected and uninfected host cells to form multinucleated giant cells. In this study, we utilized a proteomics approach to identify bacterial proteins produced inside RAW264.7 murine macrophages and host prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Further examples, pH stress and/or osmolarity stress by NaCl, provoked the secretion of type 2 and 3 secretion system-dependent proteins ( 71 , 77 ) and we found strong antibody response against BPSS1512 (TssM) and BPSS1529 (BipD), proteins secreted by a type 2 or 3 secretion system, respectively. These proteins are important for the survival inside cells because they are involved in the modulation of cell immunity or the phagosomal escape ( 78 80 ), which represent conditions of temporarily increased osmolarity and low pH.…”
Section: Discussionmentioning
confidence: 99%
“…Further examples, pH stress and/or osmolarity stress by NaCl, provoked the secretion of type 2 and 3 secretion system-dependent proteins ( 71 , 77 ) and we found strong antibody response against BPSS1512 (TssM) and BPSS1529 (BipD), proteins secreted by a type 2 or 3 secretion system, respectively. These proteins are important for the survival inside cells because they are involved in the modulation of cell immunity or the phagosomal escape ( 78 80 ), which represent conditions of temporarily increased osmolarity and low pH.…”
Section: Discussionmentioning
confidence: 99%
“…The bioinformatics analysis showed that many proteins involved in glycometabolism are changed when infected with B. pseudomallei HNBP001, which contain proteins involved in glycolysis, carbon metabolism, galactose metabolism, pentose phosphate pathway, and the fructose and mannose metabolism pathway. In early study, Welkos et al 27 have identified 160 B. pseudomallei ’s proteins in the infected RAW 264.7 cells, and 274 host proteins that were exclusively present or absent in infected cells. However, they focused on B. pseudomallei ’s proteins, constructed mutation genes and assessed their relative virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Alkyl hydroperoxide reductases such as AhpC in B. pseudomallei are frequently upregulated in bacteria during the intracellular phase of infection to survive host-derived hydrogen peroxide [ 224 ]. As a result, natural exposure to such intracellular bacteria is often associated with robust immune responses to these proteins, making them popular candidate antigens for a variety of pathogenic bacteria [ 225 , 226 , 227 ].…”
Section: Miscellaneous Protein Antigensmentioning
confidence: 99%